Cross-border enforcement of copyright: A special emphasis on court decisions and arbitral awards - Hany Salem (South Centre, 2025)
In today's digitally interconnected world, copyright infringement frequently crosses national borders, presenting complex legal challenges for effective enforcement of intellectual property rights in general, and copyright in particular. This paper examines the challenges associated with cross-border copyright enforcement, particularly the critical role of Private International Law (PIL) in the recognition and enforcement of foreign court decisions and arbitral awards. Although foundational treaties such as the Berne Convention, the TRIPS Agreement, and the WIPO Copyright Treaty establish essential principles of international copyright protection, they offer very limited guidance on resolving procedural and jurisdictional issues that arise in cross-border Copyright disputes. The analysis contends that the territorial nature of copyright law, compounded by fragmented and insufficiently developed PIL frameworks, creates legal uncertainty and inefficiency for rightsholders to secure effective remedies. To address these shortcomings, the study underscores the need for a more coherent and harmonized international PIL approach. It further explores the potential of soft law instruments - particularly the 2020 Kyoto Guidelines - as a constructive step toward resolving PIL issues related to international copyright disputes. By narrowing the gap between domestic legal systems and international enforcement mechanisms, these developments could significantly enhance legal predictability and access to justice in the global digital environment.
Keywords: 300; Urheberrecht; Immaterialgüterrechte; Internationales Recht; Internationale Schiedsgerichtsbarkeit; Rechtsdurchsetzung; Internationales Privatrecht; Welt